The Emergence of Paradigm Setters through Firms' Interaction and Network Formation - Rainer Andergassen; Franco Nardini; Massimo Ricottilli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
Technological innovation requires the gathering of information through a process of searching and learning. We distinguish two different but definitely complementary and overlapping ways through which searching and learning occur. The first exploits the spillover potential that lies in a firm's network and thanks to which gathering innovationuseful information is actually possible. The second is the autonomous capacity that a firm possesses in order to carry out in-house innovative search. We build a model where rationally bounded firms try to increase their innovative capability through endogenous networking. The paper characterizes the emergence of technological paradigm setters in terms of network properties as they result from searching routines, furthermore the corresponding average efficiency of the system in terms of innovative capability is assessed.
Keywords: 330; Technischer Fortschritt; Informationsversorgung; Lernprozess; Netzwerk; Begrenzte Rationalität; Spillover-Effekt